MODEL ASOSIASI PERUBAHAN WARNA PADA INDIKATOR KEMASAN CERDAS DAN PERUBAHAN MUTU PRODUK SUSU - Elfa Susanti Thamrin, Endang Warsiki, dan Taufik Djatna (Jurnal Teknologi Industri Pertanian, 2017)
Colour based indicator for smart packaging is important for customers to get real fresh product and minimize the risk dealing with expiry storage. Currently, there is no exact model to relate these gradual colour changes with what extend of quality rate. Thus in this paper, it proposed a model based on association rules mining to generate relationship of smart packaging colour indicator and the quality of pasteurized milk packaged on the plastic bottle. The objectives of this research were to identify association parameters and to develop an association model of discoloration of smart packaging indicator on natural dyes to the quality changes. For a complete solution, the association model was effective to predict the status of smart packaging by applying the apriory algorithm from a combination of items. This research showed applicability from the association parameters which were obtained from previous research. Furthermore, this research generated top 10 rules out of 77 significant association rules which effectively outlined the quality to discoloration relationship and had strong relationship. Hence, these rules directly were applicable for the implementation of natural dyes to construct a smart packaging indicator.Keywords: smart packaging, association rules mining, color change, quality change